THE EFFECT OF ENTERPRISE RISK MANAGEMENT DISCLOSURE, BONDING COST REDUCTION, AND MANAGERIAL OWNERSHIP ON FIRM VALUE - Kadek Naraya Yoga Semadi; Gerianta Wirawan Yasa (Adisam Publisher, 2025)
Firm value refers to the total economic value of a company and serves as an important indicator reflecting its performance, profitability potential, growth, and competitiveness in the market. This study aims to provide empirical evidence regarding the effect of enterprise risk management (ERM) disclosure, bonding cost reduction, and managerial ownership on firm value. The study was conducted on technology sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. A total of 72 observations were obtained using non-probability sampling, specifically purposive sampling. Data were collected through non-participant observation by accessing the official IDX website and the respective companies’ websites. The analytical method employed was multiple linear regression analysis. The results show that ERM disclosure and managerial ownership have a positive effect on firm value, while bonding cost reduction has no significant effect. These findings reinforce agency theory and the economics of information theory, highlighting the important role of ERM disclosure and managerial ownership in enhancing firm value through reducing agency conflicts and information asymmetry. Meanwhile, the findings regarding bonding cost reduction provide theoretical development opportunities and open avenues for evaluating the long-term effectiveness of internal monitoring mechanisms.